Failure of Reconstructive Technique to Repair a Giant Intracranial Fusiform Aneurysm of the Basilar Artery: Case Report and Literature Review in the Pediatric Population - Solis, Frank G.; Toledo, Mauro; Ecos, Rosa L. (Indian Journal of Neurosurgery, 2023)
Treatment of giant basilar aneurysm presents a major treatment challenge, especially in the pediatric population. Morbidity and mortality approach 80 and 30%, respectively. Both reconstructive and deconstructive techniques are associated with high rates of complete occlusion and good neurological outcomes. We report a 14-year-old male with a giant basilar trunk aneurysm treated with an endovascular approach. Clinical symptoms began following an ischemic stroke 2 weeks prior to admission. Endovascular treatment was performed through a reconstructive technique by single flow diverter device (FDD) in the basilar artery; however, this technique failed. At 1-year follow-up, without additional endovascular treatment, the mid-basilar artery and aneurysm were occluded, with vertebrobasilar flow maintained through collaterals from the right posterior communicating artery. We present a challenging management of giant basilar aneurysm in a pediatric patient experiencing a failure of FDD deployment; however, we highlight the importance of collateral flow development in progressive occlusions.
Keywords: endovascular approach; flow diverter device; giant basilar aneurysm